5 - Moçambique : o caso dos jor ões dos direitos humanos - Luca Bussotti (Africa Media Review, 2012)
The article aims at understanding how the Mozambican press covers the violations of human rights by the State, inside and outside prisons, focussing on the biennium 2008-2009, considering the two most common newspapers of the country, Notícias (public) and O País (independent). These two newspapers haven´t got an editorial line on human rights yet: the first one (Notícias) intends to defend the name of local institutions, considering violations as isolated individual initiatives (generally by policemen); the second one (O País) represents the Police as the worst violator of human rights in Mozambique. Hence the different approach: Notícias privileges institutional sources, while O País the “alternative” ones, using reportages, verifying the facts and, if necessary, contesting the version of authorities.